The Social Impacts of Seasonal Migration : Lessons from Australia’s Seasonal Worker Program for Pacific Islanders - World Bank (World Bank, Sydney, 2018)
The Seasonal Worker Program (SWP) is a temporary migration scheme between Australia and selected Pacific Island Countries. It was introduced in 2012 and covers the agriculture, accommodation and tourism sectors. Extensive efforts have been made to evaluate the economic impacts of the scheme, but there is a lack of evidence on the social impacts emanating from the extended absences of key family members. Moreover, of the 17,320 workers who have participated in the program since its inception, only 13.7 percent have been women. There are gaps in understanding around the gendered impact of the program and the constraints that prevent women from accessing the SWP. Based on a focus on the two largest participating countries in the scheme, Tonga and Vanuatu, this paper aims to: (i) assess both positive and negative social impacts of seasonal migration and explore how negative consequences can be mitigated; and (ii) examine the experience of women in the program, explore the barriers to access and put forward a set of recommendations to increase the female participation rate.